Hardware implementation of varicap diode's ANN model using PIC microcontrollers - Turkoglu, Ibrahim (Elsevier Science Sa, 2007)
In this paper, a hardware implementation of varicap diode's ANN model by using PIC microcontroller is presented. With this intend, reverse bias voltage of diode is used as model input and the capacitance variation of the diode is used as model output. ANN model of designed structure is realized by computer. ANN model parameters were used to build PIC microcontroller program. Then ANN model of varicap, diode was realized on PIC microcontroller. The validation of intelligent model was tested with both software and hardware. Test results are found successful. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: artificial neural networks; PIC microcontrollers; hardware implementation; varicap diode; neurocomputing